Measurement of radionuclides concentration in soil of selected regions of Kirkuk and Salahuddin - Sabah Mahmoud Aman Allah; Abdullah Zahim Nouri (Tikrit Journal of Pure Science, 2019)
The present  research aims to assess the radionuclides concentration in the soil samples by using the spectroscopy technique of high-purity germanium detector. Four samples of soil were collected at depth of 15 cm for selected regions of Kirkuk and Salahuddin governorates with two samples for the two governorates. The study shows that the activity unit for the 226Ra, 214Pb, 212Pb, 228Ac, and 40K in the studied samples ranged between (11.4±0.7-5.6±1.2) in a rate (9.4±0.85) and in a (3.8± 0.4-29±4) and rate (19.3 ± 5.4) (2± 0.1 – 9.4±0.7) in a rate (6.4±0.54) and (1.6±0.2-11.4±1.2) in a rate (7.95 ± 0.775) and (64.2 ± 4.2-226.2 ± 8) in a rate (172.25 ± 7.7) Bq.kg-1, respectively, as well as, calculated EQ Radium (60.7194-12.8314) Bq.kg-1, activity concentration indicator (  (0.4448-0.096133), internal Risk indicator (0.236988-0.049795), external risk indicator(0.164015-0.03466), values of absorbed dose in air (28.79214-6.23074) nGy.kg-1, the annual effective dose internal factor (0.141243-0.030566) mSv.y-1, the annual effective dose external factor(0.035311-0.007641) mSv.y-1. All these values do not exceed the internationally permissible standards recognized by the World Health Organization (WHO) and have no adverse impact, on the human health or the environment.